PERAN CITIZEN JOURNALISM DAN MEDIA SOSIAL DALAM AKUNTABILITAS PUBLIK MUTU PENDIDIKAN ISLAM: ANALISIS SENTIMEN DAN DAMPAKNYA TERHADAP REPUTASI INSTITUSI - Liqo Mursidah; Siti Aimah (As-Sulthan Journal of Education, 2026)
This study aims to analyze the shift of accountability for the quality of Islamic education into the digital public sphere through citizen journalism practices and the dynamics of social media sentiment. The research uses a qualitative approach with an interpretative paradigm and employs descriptive-analytical research methods. Data were collected through digital observation (netnography), documentation of social media content, in-depth interviews with pesantren leaders, social media managers, parents of students, and alumni, as well as literature studies. Data analysis was conducted thematically, combined with qualitative sentiment analysis. Meanwhile, the validity of the data was maintained through source and data triangulation. The research results show that social media has become a social evaluation mechanism that influences the formation of perceptions, trust, and the reputation of Islamic educational institutions. Experience-based citizen journalism practices encourage transparency, public participation, and more open accountability, where institutional legitimacy no longer rests solely on administrative aspects, but on the construction of collective opinion in the digital space. This study contributes to strengthening the perspective of social accountability in the management of the quality of Islamic education in the digital era.